Analysis of Factors Affecting the Potential Bankruptcy of Construction Companies Before and During Covid-19 - Alamajibuwono, Hadha; Gandakusuma, Imo (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
Every company has goals to achieve, including construction companies. However, a problem that cannot be avoided in every company is bankruptcy. This study aimed to determine differences in the financial distress of construction companies before and during the COVID-19 pandemic and whether financial and macroeconomic factors affected financial distress before and during the COVID-19 pandemic crisis. The population in this research is all construction companies on the Indonesian Stock Exchange. The sampling technique used was purposive sampling. The samples obtained were 25 construction sector companies on the Indonesia Stock Exchange during 2017-2022. The research method uses a panel data regression model involving company financial and macroeconomic factors on the financial distress of companies as measured by the bankruptcy model Altman (1968) and Ohlson (1980). The study’s results confirmed no differences between Z-scores and O-scores before and during the Covid-19 pandemic. However, there were differences in construction companies’ Z-score and O-score patterns before and during the Covid-19 pandemic. In addition, it was also found that before and during the Covid-19 pandemic crisis, only the company’s financial factors affected the Z-score and O-score model.